Needs assessment of people living with cognitive impairment/dementia, a requirement of comprehensive psychogeriatric assessment and person-centered care. Empirical validation of the model in a community study - Vicente-Alba, Javier; Gutiérrez-Botella, Jesús; García-Mahía, Carmen; Mateos, Raimundo (Frontiers in Psychiatry, 2024)
IntroductionCognitive impairment and dementia are part of a continuum that progressively leads to functional impairment and dependency. Dementia is a paradigmatic example of chronic and complex psychogeriatric diseases, requiring a comprehensive assessment. The authors underline the importance of implementing a formal assessment of needs (whether met or unmet) as an essential element of comprehensive assessment. The aim of this paper is to empirically validate this model of approach towards dementia, the needs assessment, demonstrating the relationship between needs and functionality/dependency in people with cognitive impairment/dementia in the community.Material and methodsCommunity-based, cross-sectional, descriptive epidemiological study based on the reanalysis of data from a two-phase community epidemiological study conducted in Santiago de Compostela, Spain, of 800 people over 65 years of age. The present study reanalyzes a subsample of 368 people, including those with dementia/cognitive impairment. The comprehensive assessment of the sample included sociodemographic variables, the presence of chronic diseases, health self-perception, assessment of affective, cognitive and functional state, as well as the needs assessment. The main instruments used were the MMSE, the Geriatric Depression Scale (GDS), the Barthel and Katz Indices, the Lawton Scale, and, for the needs assessment, the Camberwell Assessment of Need for the Elderly (CANE). For the clinical diagnosis of dementia, the ICD-10 criteria were followed. Statistical analysis: A study of the association between variables was carried out through hypothesis testing and a multivariate study was performed using regression models to analyze the relationship between the different variables defining disability/dependency, other health conditions and sociodemographic variables and the MMSE score as an expression of the cognitive impairment/dementia continuum.ResultsPeople with cognitive impairment/dementia had a higher number of needs compared to the healthy population. The severity of cognitive impairment is a significant predictor of dependency in Basic Activities of Daily Living (BADL) and is also a predictor of a greater number of needs (both met and unmet).DiscussionThe present study provides empirical evidence of the importance of implementing scales to assess the needs of people with cognitive impairment, as part of the process of comprehensive biopsychosocial assessment and person-centered care for dementia.